Innovation and Entrepreneurship in Colleges: An Interpretive Study of the Piloting of Innovation Centres - McWilliam, Carol L. (Canadian Journal of Higher Education, 1990)
The implications of college involvement in innovation and entrepreneurship through centres which promote such directions have as yet received little consideration. This interpretive study examines the sociocultural context of Ontario Colleges at the macro, medial, and micro levels of the organization. Findings describe government fiscal policy, profitability motives, bureaucratic organizational norms, incrementalism, and political and power relationships impeding successful integration of innovation centres into colleges. Such factors have precluded consideration of several significant philosophical issues. Privatization of college education, the research, community service and teaching roles of colleges, and the socialization role which colleges might play in inculcating values and skills associated with innovation and entrepreneurship have yet to be examined. Clearly, if colleges are to achieve purposeful direction-setting for the future, all involved with this system must engage in interactive leadership to decide upon values, motives and educational philosophy related to innovation and entrepreneurship.